Rituximab versus an alternative TNF inhibitor in patients with rheumatoid arthritis who failed to respond to a single previous TNF inhibitor: SWITCH-RA, a global, observational, comparative effectiveness study. Issue 6 (17th January 2014) - Emery, P; Gottenberg, J E; Rubbert-Roth, A; Sarzi-Puttini, P; Choquette, D; Taboada, V M Martínez; Barile-Fabris, L; Moots, R J; Ostor, A; Andrianakos, A; Gemmen, E; Mpofu, C; et al.
Abstract : Objectives: To compare the effectiveness of rituximab versus an alternative tumour necrosis factor (TNF) inhibitor (TNFi) in patients with rheumatoid arthritis (RA) with an inadequate response to one previous TNFi. Methods: SWITCH-RA was a prospective, global, observational, real-life study. Patients non-responsive or intolerant to a single TNFi were enrolled ≤4 weeks after starting rituximab or a second TNFi. Primary end point: change in Disease Activity Score in 28 joints excluding patient's global health component (DAS28-3)–erythrocyte sedimentation rate (ESR) over 6 months. Results: 604 patients received rituximab, and 507 an alternative TNFi as second biological therapy. Reasons for discontinuing the first TNFi were inefficacy (n=827), intolerance (n=263) and other (n=21). A total of 728 patients were available for primary end point analysis (rituximab n=405; TNFi n=323). Baseline mean (SD) DAS28-3–ESR was higher in the rituximab than the TNFi group: 5.2 (1.2) vs 4.8 (1.3); p<0.0001. Least squares mean (SE) change in DAS28-3–ESR at 6 months was significantly greater in rituximab than TNFi patients: −1.5 (0.2) vs −1.1 (0.2); p=0.007. The difference remained significant among patients discontinuing the initial TNFi because of inefficacy (−1.7 vs −1.3; p=0.017) but not intolerance (−0.7 vs −0.7; p=0.894). Seropositive patients showed significantly greater improvements in DAS28-3–ESR with rituximab than with TNFi (−1.6 (0.3) vs −1.2 (0.3); p=0.011), particularly those switching because of inefficacy (−1.9 (0.3) vs −1.5 (0.4); p=0.021). The overall incidence of adverse events was similar between the rituximab and TNFi groups. Conclusions: These real-life data indicate that, after discontinuation of an initial TNFi, switching to rituximab is associated with significantly improved clinical effectiveness compared with switching to a second TNFi. This difference was particularly evident in seropositive patients and in those switched because of inefficacy.